HADIS SAâAD IBN ABI WAQASH TENTANG WASIAT SEPERTIGA HARTA KEKAYAAN - Bahdar, Bahdar (Hunafa: Jurnal Studia Islamika, 2005)
This article deals with portion of inheritance in Islamic law (syariâah). Portion of inheritance intended in it is that occurs in the case ofÂ  Saâad Abi Waqash who wishes to inherit his whole property. For this purpose, he conveys his willingness to the Messenger in order that he can get legitimization. However, the prophet rejects his willingness to inherit his whole property but permits him to inherit one-third of itÂ Kata Kunci:Â  Wasiat, Harta Kekayaan, Saâad bin Abi Waqash